2020
DOI: 10.1080/01431161.2020.1757783
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of remote sensing-based drought index over different land cover types in southern Africa

Abstract: An understanding of drought and land cover interaction plays a crucial role in vegetation vulnerability studies and land use planning. However, there is paucity of information on drought, land cover and land use interaction in southern Africa. We analysed the drought impact on land cover using Globcover land cover data and Vegetation Condition Index (VCI) for the 2015 to 2016 season. The 2015 to 2016 season was chosen because it was the worst drought in southern Africa since the 1980s. We developed a novel lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…The q values for the interaction effect between the vegetation type and soil texture factors on the best time lag of the NPP response to PPT and Ta were all greater than those for a single factor (Table 2), which indicated that the interaction effect between the vegetation type and soil texture factors was bivariable enhanced. In line with the findings of other researchers [16,55,56], there occurred a notable legacy effect of climate conditions, where vegetation growth was significantly affected by PPT, Ta, and SPEI in preceding months. Previous studies of ecotones determined that the ecotone migration response to climate warming was gradual, exhibiting a lag effect due to the resistance of retreating forest biomes [28].…”
Section: Time-lag Effects Of Climate Conditions On Npp With Vegetatio...supporting
confidence: 91%
See 2 more Smart Citations
“…The q values for the interaction effect between the vegetation type and soil texture factors on the best time lag of the NPP response to PPT and Ta were all greater than those for a single factor (Table 2), which indicated that the interaction effect between the vegetation type and soil texture factors was bivariable enhanced. In line with the findings of other researchers [16,55,56], there occurred a notable legacy effect of climate conditions, where vegetation growth was significantly affected by PPT, Ta, and SPEI in preceding months. Previous studies of ecotones determined that the ecotone migration response to climate warming was gradual, exhibiting a lag effect due to the resistance of retreating forest biomes [28].…”
Section: Time-lag Effects Of Climate Conditions On Npp With Vegetatio...supporting
confidence: 91%
“…Previous studies of ecotones determined that the ecotone migration response to climate warming was gradual, exhibiting a lag effect due to the resistance of retreating forest biomes [28]. This result is similar to ours in the considered forest-grassland ecotone, and details and a comparison are provided in Table 3 [16,55,[57][58][59][60]. In previous studies of the time-lag effect, the time lag ranged from 6.2 days to 9 months at the daily, monthly, and annual scales.…”
Section: Time-lag Effects Of Climate Conditions On Npp With Vegetatio...supporting
confidence: 84%
See 1 more Smart Citation
“…El Niño is characterized by a positive and significant anomaly of SST in the equatorial Pacific Ocean near South America. The Southern Oscillation is an interannual fluctuation of atmospheric pressure at sea level over the Pacific Ocean, usually evaluated with the Southern Oscillation Index (SOI), which is a standardized index based on the sea level pressure (SLP) differences between Tahiti and Darwin, Australia [48,55,65].…”
Section: Drought Factorsmentioning
confidence: 99%
“…Single or combined, these indices can assign droughts identification with respect to duration, severity, intensity, and location (Heim, 2002;Keyantash and Dracup, 2002). Although the standardized precipitation index (SPI), a precipitation-based index, is the most commonly used, remote sensing-based indices are increasingly important tools for droughts monitoring as they can surpass the limitations of other indices which often require multiple and serially complete data (Hazaymeh and Hassan, 2017;Marumbwa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%